2017
DOI: 10.18203/2349-2902.isj20174885
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative safety of low pressure pneumoperitoneum cholecystectomy: a comparative study

Abstract: Background: With the establishment of laparoscopic cholecystectomy as gold standard for management of cholelithiasis, the current stress is on increasing patient safety. Hence, this study was undertaken to compare the effect of low pressure pneumoperitoneum (LPP <10mm Hg) versus high pressure pneumoperitoneum (HPP >14mm Hg) in a prospective randomized manner on intraoperative safety, assessing the working space and safety by seeing contact of parietal peritoneum to underlying viscera during secondary por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Mahajan et.al suggested to standardize low-pressure laparoscopic cholecystectomy in day care surgery, as they found the procedure to be safe and feasible, with no signi cant difference when compared to standard pressure pneumoperitoneum in terms of adequacy of surgical eld, contact of parietal peritoneum to the underlying viscera during secondary port insertion, duration of surgery, complication rates, and surgery di culty. 13 In this trial the total operative time, insu ation time and total hospital stay was similar across both groups. None of the patients had major intraoperative complication, 30-day mortality rate was zero in both groups, only 3 patients in the low-pressure group had a change from initial set pressure point, and 4…”
Section: Discussionmentioning
confidence: 59%
“…Mahajan et.al suggested to standardize low-pressure laparoscopic cholecystectomy in day care surgery, as they found the procedure to be safe and feasible, with no signi cant difference when compared to standard pressure pneumoperitoneum in terms of adequacy of surgical eld, contact of parietal peritoneum to the underlying viscera during secondary port insertion, duration of surgery, complication rates, and surgery di culty. 13 In this trial the total operative time, insu ation time and total hospital stay was similar across both groups. None of the patients had major intraoperative complication, 30-day mortality rate was zero in both groups, only 3 patients in the low-pressure group had a change from initial set pressure point, and 4…”
Section: Discussionmentioning
confidence: 59%
“…Our trial supports similar results even in the hands of non-experienced surgeons. Mahajan et al suggested to standardize low-pressure laparoscopic cholecystectomy in day care surgery, as they found the procedure to be safe and feasible, with no significant difference when compared to standard pressure pneumoperitoneum in terms of adequacy of surgical field, contact of parietal peritoneum to the underlying viscera during secondary port insertion, duration of surgery, complication rates, and surgery difficulty [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The standard pressure in pneumoperitoneum is 12-14 mmHg; it is also associated with complications that usually happen following the prolonged and difficult surgeries due to head-down position and pneumoperitoneum; for example, reduced lung capacity, hemodynamic complications, changes in the concentration of arterial blood gases, increased liver enzymes, renal failure, post-operative abdominal and shoulder-tip pain. [4][5][6] Recently, to reduce the complications, surgeons tend to use gases with 7-10 mmHg pressure instead of the standard high pressure. Using lower pressure obtains good results such as less post-op abdominal and shoulder tip pain, less pulmonary complications.…”
mentioning
confidence: 99%